Our Ancient Forests: Virtual Visiting and Art for Conservation - Morgan-Thorp, Emma (Performance Matters, 2021)
This article reflects upon two virtual reality experiences included in the Our Ancient Forests exhibition at the Sunshine Coast Arts Council: Sanctuary: The Dakota Bear Ancient Forest Experience and Tree Earth Sky. It works through questions about the use of virtual reality both as a means of visiting a wild place and as a means of moving audiences to environmentalist and anticolonial action. In doing so, it considers settler desires for deeper relationships with wild places and the more-than-human world and settler responsibilities within environmental and anticolonial movements.